Appraisal of Indigenous People in the Historical Account of Heritage Cities: The Case of la Serena (Chile); [Valoraciones Sobre Los Indígenas en el Relato Histórico de Ciudades Patrimoniales: El Caso de la Serena (Chile)] - Cortes-Ferreira, C (Universidad de la Serena,Departamento de Artes y Letras, 2023)
The study of heritage as a sociocultural phenomenon requires paying attention to the representations that are elaborated and the way they circulate socially. In the case of this article, the problem identified is that the historical recounts used in the dissemination of historical and heritage cities could be negatively representing indigenous peoples, collaborating in the reproduction of this representations. Framed as a case study of the city of La Serena (Chile), this article aims to identify the appraisal about indigenous peoples in historical recounts. Patrimonial Studies and Critical Discourse Studies are used theoretically, opting for the theoretical architecture of Systemic-Functional Linguistics whose Appraisal system allows us to investigate the rhetorical effects that build ideological positions in the speeches. It is concluded that the historical recounts have a traditional ideological positioning of History, since the narration is presented as a story of Hispanic heroes who face great deeds against the indigenous people, whose participation is decontextualized and reduced to the destruction of the city and the opposition to the Spanish conquers. © 2024 Gurskaya et al.